Avenanthramides attenuate inflammation and atrophy in muscle cells - Dongwook Yeo; Chounghun Kang; Tianou Zhang; Li Li Ji (Elsevier, 2019)
Background: Chronic inflammation is an important etiologic mechanism for muscle atrophy. Oat-derived phytochemical avenanthramides (AVAs) have been shown to suppress inflammatory responses in human clinical studies and in several cell lines in vitro, but their role in skeletal muscle is unclear. The aim of this study was to investigate whether AVA treatment can prevent tumor necrosis factor (TNF)-α-induced muscle fiber atrophy in C2C12 cells. Methods: We treated 70% confluent cells for 24 h with AVA. Then, TNF-α was added to cell-cultured medium. Subsequently, cells were harvested at different time points. The cells were examined using various biochemical techniques for measuring protein, messenger RNA levels, nuclear binding activity, and viability. Fluorescence microscope was used for analysis of the myotube morphology. Results: Cells treated with TNF-α significantly increased nuclear factor κB activation, indicated by a marked decrease of IκB (p < 0.05) and a 6.6-fold increase in p65-DNA binding (p < 0.01); however, 30 μmol of AVA-A, -B, and -C treatment reduced the binding by 33%, 18%, and 19% (p < 0.01), respectively, compared with cells treated with TNF-α without AVA. The interleukin-6 level increased by 2.5 fold (p < 0.01) with TNF-α, but decreased by 24%, 32%, and 28% (p < 0.01), respectively, with AVA-A, -B, and -C. The interleukin-1β level also showed a 47% increase with TNF-α (p < 0.01), whereas this increment was abolished in all AVA-treated cells. Reactive oxygen species production was 1.3-fold higher in the TNF-α-treated group (p < 0.01) but not in the TNF-α + AVAs groups. Messenger RNA levels of muscle-specific E3 ubiquitin ligase atrogin-1 increased 23% in TNF-α vs. control (p < 0.05) but was decreased by 46%, 34%, and 53% (p < 0.01), respectively, with treatment of AVA-A, -B, and -C. Moreover, TNF-α treatment increased the muscle RING finger 1 messenger RNA level by 76% (p < 0.01); this change was abolished by AVAs. Cells treated with TNF-α demonstrated a reduced proliferation compared with control cells (p < 0.01), but this effect was not seen in TNF-α + AVAs cells. The diameter of the C2C12 myotube decreased by 28% (p < 0.01) with TNF-α, whereas it showed no change when AVAs were included in the cell media. Conclusion: These results indicated that AVAs can reduce proinflammatory cytokine and reactive oxygen species production and ameliorate TNF-α-induced myotube atrophy in muscle cells. Keywords: Atrogenes, Interleukin, NF-κB, Skeletal muscle, TNF-α